KESEIMBANGAN HIDUP DAN KELELAHAN EMOSIONAL SEBAGAI PENENTU KINERJA PERAWAT RUMAH SAKIT SWASTA - Mettatirtha, Rosalina; Septiana, Agatha (Jurnal Keuangan dan Bisnis, 2025)
Purpose: This study aims to examine the effects of work life balance and emotional exhaustion on in-role performance among nurses working in private hospitals in Palembang City. The research highlights the significance of maintaining life work balance and managing emotional fatigue in enhancing nurses’ performance effectiveness. Design/Methodology/Approach: A quantitative research approach was employed using a survey method. Data were collected from 112 nurses across various private hospitals in Palembang. Multiple linear regression analysis was performed using SPSS to test the direct relationships among variables. Findings: The results reveal that work life balance has a positive and significant effect on in-role performance, whereas emotional exhaustion has a negative and significant effect. These findings suggest that balanced work–life integration improves nurses’ job performance, while emotional fatigue reduces their motivation, focus, and productivity. Practical Implications: The results emphasize the need for hospital management to develop human resource policies that promote work–life balance and emotional well-being, such as optimized shift scheduling, supportive leadership, and psychological support programs. These efforts can enhance nurses’ performance and service quality in healthcare institutions. Originality/Value: This study contributes to human resource management literature in the healthcare sector by integrating psychological and behavioral dimensions work life balance and emotional exhaustion as dual determinants of in-role performance. It provides empirical insights into the performance dynamics of nurses in Indonesia’s private hospital context.